POPULATION AND OCCUPATIONAL CHANGE IN A COASTAL VILLAGE - Nurdien H. Kistanto (JOURNAL OF COASTAL DEVELOPMENT, 2000)
In “Sumbersari” there are three major types of productive work: rice farming , fish raising and factory work. The industrial estate which has been operating since the late 1970s has altered the pattern of employment, in part because the agricultural land previously used for rice fields and brackish water ponds has been converted to industrial use. Waves of migrants from other places have taken up residence in Sumbersari either on a temporary or a permanent basis. These migrants have contributed to population growth and comprise he bulk of work force in this village.